Dalla costruzione del capro espiatorio al primato della responsabilità personale: il caso Eatherly - Trupiano, Antonio (Rassegna di teologia, 2025)
The construction of the scapegoat is always connected to a cultural crisis, the spread of mimicry and a void of personal responsibility. Starting from this observation, the Author explores the complex "Eatherly case" which, thanks to the epistolary exchange initiated by Günther Anders, has undergone radical transformations: the young American pilot first tries to atone for his terrible guilt, then becomes the victim of all those who challenge him for the suffering he feels torn apart by, finally he interrupts the scapegoat mechanism by handing over his freedom in the service of an unbreakable commitment against war.